[68Ga]Ga-DOTA-TOC: The First FDA-Approved 68Ga-Radiopharmaceutical for PET Imaging - Ute Hennrich; Martina Benešová (MDPI AG, 2020)
In the United States, [68Ga]Ga-DOTA-TOC has been approved by the Food and Drug Administration (FDA) in 2019 as the first 68Ga-radiopharmaceutical for imaging of somatostatin receptor (SSTR) positive gastroenteropancreatic neuroendocrine tumors while employing positron emission tomography (PET). In Europe (Austria, Germany, France), [68Ga]Ga-DOTA-TOC was already approved back in 2016. This radiopharmaceutical combines the radionuclide 68Ga with the somatostatin analogue DOTA-TOC for specific imaging of tumor cells expressing SSTRs. Such a targeting approach can also be used for therapy planning in the case of both localized as well as disseminated disease and potentially for the evaluation of treatment response.